Design engineer's reference guide : mathematics, mechanics, and thermodynamics - Richards, Keith L. (CRC Press, 2014)
Author Keith L. Richards believes that design engineers spend only a small fraction of time actually designing and drawing, and the remainder of their time finding relevant design information for a specific method or problem. He draws on his own experience as a mechanical engineering designer to offer assistance to other practicing and student engineers facing the same struggle. Design Engineer's Reference Guide: Mathematics, Mechanics, and Thermodynamics provides engineers with a roadmap for navigating through common situations or dilemmas.